CacyBP/SIP protein is important for the proliferation of human glioma cells. Issue 4 (17th April 2014) - Shi, Hengliang; Gao, Yong; Tang, Yuan; Wu, Yuxuan; Gong, Hui; Du, Jin; Zheng, Bao; Hu, Jinxia; Shi, Qiong; Yu, Rutong
Abstract Recently, calcyclin‐binding protein or Siah‐1‐interacting protein (CacyBP/SIP), a component of a novel ubiquitinylation pathway, could regulate the β‐catenin degradation (Fukushima et al., Immunity 2006, 24, 29 – 39). However, the potential role of CacyBP/SIP itself in human glioma cells has not been clarified. Here, we found that CacyBP/SIP was expressed highly in human glioma tissues. Silencing of CacyBP/SIP by short‐hairpin RNA severely suppressed the proliferation of human glioma cell U251, which was at least partly mediated by downregulation of phospho‐Akt (p‐Akt) and phospho‐β‐catenin (p‐β‐catenin) as well as upregulation of p53 and p21. Furthermore, overexpression of CacyBP/SIP obviously promoted the proliferation of human glioma U251, which exhibited the exactly contrary trend in the expression of p‐Akt, p‐β‐catenin, p53, and p21. Taken together, these findings suggest that CacyBP/SIP plays important roles in the proliferation of human glioma cell which might be involved in the development of human glioma. © 2014 IUBMB Life, 66(4):286–291, 2014